The Role of Deli Serdang Police Investigators in Handling the Occurrence of Laka Lantas - Rasidin Saragih; Rahul Ardian Fikri; Abdul Razak Nasution (International Journal of Society and Law, 2024)
Traffic accidents remain a significant concern in Indonesia, particularly in Deli Serdang, where the number of cases continues to rise. This study examines the role of Deli Serdang Police investigators in handling traffic accident cases, focusing on their tasks, challenges, and efforts to ensure effective legal processes. The research highlights that investigators play a crucial role in conducting comprehensive investigations, gathering evidence, and determining legal accountability in each case. However, investigators face numerous obstacles, including limited resources, insufficient evidence, and environmental factors that complicate the investigative process. The study underscores the importance of collaboration between law enforcement and the community, as well as the need for enhanced investigator training and public education on traffic safety to mitigate accidents.